Quality assessment and political will : a necessary symbiosis - Giambruno, Cynthia (Language and Law / Linguagem e Direito, 2017)
The focus in the eld of legal interpreting is shifting from simply complying with international and national mandates on the provision of interpreting services in judicial settings to addressing issues of quality assurance. In this paper, the argument is made that qualifying individuals to work as legal interpreters is pivotal to achieving the legal certainty that is required in judicial systems today, and that positive political will and administrative action are necessary to ensure that valid certication procedures are supported and funded. A critical analysis is presented of some common elements of current assessment practices in a number of countries, together with examples of the eects of positive and negative political will.